Community Empowerment in Structuring Sustainable Historical Tourism Areas - Inayatul Fikriyah; Surjono; Johannes Parlindungan Siregar (PT FORMOSA CENDEKIA GLOBAL, 2023)
Three aims of the study are: to identify the socio-economic and socio-spatial characteristics that make up the historical tourism ecosystem in the historical area of Trowulan; to analyse community participation in building the tourism ecosystem in the historic area of Trowulan; and to formulate directives on community empowerment to increase local resources' potential and capacity through developing historical tourism businesses. The method used in this research is a qualitative method with a descriptive-analytical approach, a research and understanding process based on a methodology that investigates a social phenomenon and human problem. The research concludes that socio-economic and socio-spatial characters encourage each other in shaping the historical tourism ecosystem in the historical area of Trowulan. In addition, community participation in building a tourism ecosystem in the historic Trowulan area is motivated by the hope of getting a better economic life to improve the welfare of the community. Community empowerment is essential in increasing community participation in developing the potential and capacity of local resources through developing tourism businesses, especially those based on historical tourism. Community empowerment and participation are two entities that need each other. On the one hand, participation requires empowerment, and on the other hand, empowerment requires participation. The absence of one can hinder efforts to develop tourist areas